2021
DOI: 10.1002/dvdy.406
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the human dental follicle: From tooth development to its association with unerupted or impacted teeth and pathological changes

Abstract: Dental follicles are involved in odontogenesis, periodontogenesis, and tooth eruption. Dental follicles are unique structures, considering that their remnants can persist within the jawbones after odontogenesis throughout life if the tooth does not erupt. Pathological changes may occur in these tissues as individuals age. The changes range from benign to life threatening. Thus, the assessment of age-related changes in dental follicles associated with unerupted teeth is of paramount importance. In this review, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 135 publications
(212 reference statements)
2
25
0
5
Order By: Relevance
“…During mixed dentition, permanent tooth eruption occurs in chronological order, thereby providing an occlusal connection. A delayed, accelerated, or modified eruption sequence could be associated with malocclusions [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During mixed dentition, permanent tooth eruption occurs in chronological order, thereby providing an occlusal connection. A delayed, accelerated, or modified eruption sequence could be associated with malocclusions [4].…”
Section: Discussionmentioning
confidence: 99%
“…The eruption is a dynamic process that begins at the initial positioning of the tooth in the alveolar bone and continues until the final positioning at which it is occluded by a dental antagonist. This is an important part of the developmental period [4]. MIH, which is thought to occur in relation to factors encountered in the development process, appears to be an important health problem.…”
Section: Introductionmentioning
confidence: 99%
“…However, additional biological processes are also related to the cellular senescence of DFCs. Bastos et al showed that metabolic processes are highly regulated in senescent dental follicles [ 12 ]. This result correlates very well with the role played by the osteogenic transcription factor ZBTB16 in the osteogenic differentiation of DFCs and in crucial metabolic processes [ 120 , 121 , 122 ].…”
Section: Molecular Mechanisms Of the Osteogenic Differentiation Of Dfcsmentioning
confidence: 99%
“…While the exact role remains elusive, several tooth eruption factors have been discovered in the dental follicle over time. These include parathyroid hormone-related protein (PTHrP), epidermal growth factor (EGF), interleukin (IL)-1α, colony-stimulating factor-1 (CSF-1), monocyte chemotactic protein-1 (MCP-1) and their respective receptors, proto-oncogenes, and transcription factors such as c-Fos, nuclear factor-kappa B 1 (NFκB1) [ 10 , 11 , 12 ]. Two of these factors, PTHrP and NFκB1, which are induced by RANK/RANKL (Receptor activator of nuclear factor kappa-Β/-ligand), are also involved in the osteogenic differentiation of dental follicle cells and their functions in this context are discussed in more detail below.…”
Section: Introductionmentioning
confidence: 99%
“…As early as around tenth week of the embryonic period, the tooth germ begins to develop, which is composed of the ectoderm‐derived enamel organ, and the ectomesenchyme‐derived dental papilla and dental follicle (also known as dental sac). The dental follicle stem cells (DFSCs) are able to differentiate into cementoblasts, fibroblasts, and osteoblasts, giving rise to the formation of cementum, PDL, and alveolar bone proper respectively (Bastos, Gomez, & Gomes, 2022). While, the rest of the alveolar bone originates from neural crest derived ectomesenchyme.…”
Section: Development Of Periodontal Tissuesmentioning
confidence: 99%